Edukasi Stoma Booth Camp pada Pasien dengan Kanker Buli Paska Radikal Sistektomi - Wulandari Wulandari; Lestari Sukmarini (Jurnal Keperawatan Silampari, 2022)
This study aims to improve the ability of nurses, patients, and caregivers to treat stoma physically and psychologically. The research method used is a case study in patients who will undergo urostomy due to bladder cancer and their companions to attend SBC 2 hours before the procedure. The results of the case study after 4 weeks after treatment the patient said he had been able to replace the stoma independently. In conclusion, SBC in patients with urostoma can affect individual coping styles and maintain the quality of life of patients with ostomy. Keywords: Bladder Cancer, SBC, Stoma